2019
DOI: 10.1007/s10342-019-01212-3
|View full text |Cite
|
Sign up to set email alerts
|

Does railway noise affect forest birds during the winter?

Abstract: The construction of new railway routes and the modernisation of existing ones usually have an adverse effect on the natural environment in the vicinity of such transport corridors. Negative effects of the construction of the railway line can be observed even at a considerable distance. The high frequency of wildlife-train-collisions (wtc) can lead to the death of many animals. Many groups of animals, including birds, are exposed to noise, which modifies their densities in the neighbourhood of railway lines. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Though the noise from busy roadside traffic provides negative impact on many bird species (Rheindt 2003, Summers et al 2011, in our study, we did not observe any negative interactions with the train movements to their surroundings. Such bird species frequently observed in station areas did not react much in response to the noise made by the movement of trains through the station (Wiącek et al 2015(Wiącek et al , 2019(Wiącek et al , 2020. In the present observations, the railway stations across urban-rural gradient appear to bear a positive impact on the bird species assemblages.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Though the noise from busy roadside traffic provides negative impact on many bird species (Rheindt 2003, Summers et al 2011, in our study, we did not observe any negative interactions with the train movements to their surroundings. Such bird species frequently observed in station areas did not react much in response to the noise made by the movement of trains through the station (Wiącek et al 2015(Wiącek et al , 2019(Wiącek et al , 2020. In the present observations, the railway stations across urban-rural gradient appear to bear a positive impact on the bird species assemblages.…”
Section: Discussioncontrasting
confidence: 48%
“…The power lines, over bridge pillars, station railing borders, lamp posts possibly provide the suitable sites for chasing the prey by carnivores and insectivores (Morelli et al 2014). The anthropogenic constructions somehow attract a large number of opportunist bird species by offering environmental heterogeneity (Morelli et al 2014, Kaiser-Bonk et al 2019, Wiącek et al 2019. In this study, it was evident that the anthropogenic structures can be utilized to attract species too effectively to increase diversity irrespective to urban-rural gradient.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, some research has indicated that despite anthropogenic pressure, many animals, including birds, live in the neighbourhood of humans and their infrastructure [16,28,29,30]. The areas around railway lines and their infrastructure offer favourable conditions for birds during the breeding season [5,16,30] migration (this study) and wintering [31]. The high diversity of habitats available in transport corridors is a particularly important factor encouraging birds to nest near railway lines.…”
Section: Introductionmentioning
confidence: 87%
“…We expected that birds would prefer the vicinity of the line, as had been the case during the breeding season [5]. Therefore the alternative hypothesis assumed that, in view of the positive effects of the railway that we noted in previous studies, we should expect increasing numbers and species richness of birds in its vicinity [5,31].…”
Section: Introductionmentioning
confidence: 88%